Intensive Rehabilitation is better when it is combined with Tizanidine in Spastic Cerebral Palsy- A Randomized Clinical Trial - Amin, Md Ruhul; Banik , Amitav; Rahman, Mohammad Anisur; Rahman , Sohely (Bangladesh Journal of Medicine, 2023)
Background: To find out the combined efficacy of Tizanidine and intensive rehabilitation in the treatment of spastic cerebral palsy. Methods: This randomized clinical trial was conducted over 70 patients in Sir Salimullah Medical College Hospital from January 2022 to December 2022.The patient satisfying the inclusion and exclusion criteria was randomly enrolled into two groups; Group- A (Case) included 35 patients received only intensive rehabilitation and Group- B (Control). included 35 patients who received Tizanidine (2mg) orally at a dose of 1 mg given at bed time under 10 years and 2 mg 10 years or more, then after 1 week maintenance dose was 0.3 mg/kg/day three times daily in combination with intensive rehabilitation 1 hour daily five times a week for 24 weeks. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks. Combination of Tizanidine and intensive rehabilitation has superior efficacy in reducing tone in spastic cerebral palsy over only rehabilitation measured by using Modified ashworth scale (p<0.001). Results: Combination of Tizanidine and intensive rehabilitation is improved in physician rating scale crouch (p<0.0001) and foot contact, (p<0.0001) and also improvement in gross motor function (p<0.01). Conclusion: Combination of Tizanidine and intensive rehabilitation group has superior efficacy than only rehabilitation group for reduction of generalized spasticity regarding muscle tone, range of motion of the joint and improvement of gait in cerebral palsy patients. Bangladesh J Medicine 2023; 34(2): 98-104